2017
DOI: 10.1097/pec.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Energy Drink Use and Reported Adverse Effects Among Adolescent Emergency Department Patients

Abstract: Both brand name and packaging influenced the choice of energy drink in most subjects. Forty percent reported at least 1 adverse effect. While most adverse effects were not severe, a small number are serious. In addition, we showed intentional ingestion with ethanol and illicit drugs. Of additional concern is that both brand and packaging seem to directly affect choice of energy drink consumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Energy drinks are often marketed as providing a quick boost of energy, which may attract the attention of adolescents who may be going through exams, sport season, and end of the school year party season. In a sample of adolescents aged 13-19 years utilizing emergency department services for any reason, Nordt et al [39] identified several reasons for energy drink consumption, including to increase energy (61%), as a study aid (32%), to improve sports performance (29%), and to lose weight (9%). However, energy drink consumption can have negative effects on health, such as dehydration, arrythmia, heart failure, anxiety, and insomnia [40].…”
Section: Comparison With Other Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Energy drinks are often marketed as providing a quick boost of energy, which may attract the attention of adolescents who may be going through exams, sport season, and end of the school year party season. In a sample of adolescents aged 13-19 years utilizing emergency department services for any reason, Nordt et al [39] identified several reasons for energy drink consumption, including to increase energy (61%), as a study aid (32%), to improve sports performance (29%), and to lose weight (9%). However, energy drink consumption can have negative effects on health, such as dehydration, arrythmia, heart failure, anxiety, and insomnia [40].…”
Section: Comparison With Other Literaturementioning
confidence: 99%
“…Our results showed that 42.1% of adolescents who reported alcohol consumption in the past 12 months also reported energy drink consumption in the past 12 months, compared to only 18.6% of those who did not report alcohol consumption. There is also evidence of mixing energy drinks with cannabis and prescription drugs [39,40]. For example, Nordt et al [39] found that 24% of adolescents who visited emergency room for any reason reported using energy drinks with ethanol or drugs, such as cannabis, cocaine, and methamphetamine.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A faixa etária da amostra mostrou-se composta predominantemente por adultos jovens, de 18 a 25 anos (71%), assim como encontrado por Silva e Marins¹. A procura por SA é comum nessa faixa etária, considerando a facilidade de acesso à informação e compra desses produtos, além do apelo midiático direcionado para este público, que compõe a maior parte dos frequentadores de academias com objetivos estéticos, sendo uma população com maior participação em mídias sociais, local onde a pesquisa foi divulgada, diferentemente de trabalhos como o de Nordt et al 16 , que obteve dados presencialmente. como objetivo principal a manutenção da saúde (32,7%), seguida por estética (27,4%) e melhora do condicionamento físico (25,9%).…”
Section: Discussionunclassified
“…Concerns have been raised about the indiscriminant use of EDs and ESs. [61][62][63][64] This includes concern about the use of EDs to counteract the depressive effects of alcohol, which, may lead to excessive alcohol intake and/or intoxication. 59,[65][66][67][68][69] For example, several studies suggest that individuals who mix alcohol with EDs are more likely to consume more alcohol and/or engage in risky behaviors.…”
mentioning
confidence: 99%